The Coxeter group Dn - M. A. Albar; Norah Al-Saleh (International Journal of Mathematics and Mathematical Sciences)
We show that the Coxeter group Dn is the split extension of n−1 copies of Z2 by Sn for a given action of Sn described in the paper. We also find the centre of Dn and some of its other important subgroups.